Interactions access : - Hartmann, Pamela (McGraw-Hill, 1997)
This text combines reading and writing skills in one text. After completing the first parts of any chapter, students will have a firm base of vocabulary, grammar, and ideas needed for completing the writing exercises in Part Four. Ideal for pre-beginning to beginning ESOL students.